2020
DOI: 10.1111/desc.13012
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary pursuit of negatively valenced stimuli from childhood to early adulthood

Abstract: Although common sense suggests that we are motivated to pursue positive and avoid negative experiences, previous research shows that people regularly seek out negative experiences. In the current study, we characterized this tendency from childhood to young adulthood. Due to the known increases in risky behavior and sensation seeking in adolescence, we hypothesized that adolescents would show an increased engagement with negatively valenced stimuli compared to children and adults. Participants aged 4–25 (N = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Even 3-year-olds used negativity to guide their sorting behaviors, although this result should be interpreted cautiously given how this age group approached the practice sort (see Section 1 of Supporting Information ). Our findings of an early role for negativity in children’s emerging emotion knowledge is consistent with reports that young children display greater knowledge of negative emotions ( Lagattuta & Wellman, 2001 ), attend more to negative faces ( Lagattuta & Kramer, 2017 ), engage in greater discussion of negative emotions ( Lagattuta & Wellman, 2002 ), and voluntarily explore negatively valenced stimuli ( Grisanzio et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Even 3-year-olds used negativity to guide their sorting behaviors, although this result should be interpreted cautiously given how this age group approached the practice sort (see Section 1 of Supporting Information ). Our findings of an early role for negativity in children’s emerging emotion knowledge is consistent with reports that young children display greater knowledge of negative emotions ( Lagattuta & Wellman, 2001 ), attend more to negative faces ( Lagattuta & Kramer, 2017 ), engage in greater discussion of negative emotions ( Lagattuta & Wellman, 2002 ), and voluntarily explore negatively valenced stimuli ( Grisanzio et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that people were sometimes motivated to see negative stimuli over positive stimuli and chose to see a negative image with moderate probability. These findings have also been observed in children (Grisanzio et al, 2021).…”
Section: Morbid Curiositysupporting
confidence: 78%
“…This needn't occur out of necessity, as the proportion of negative or positive words that people know or can rapidly generate could vary for different age groups (e.g., children could know many more negative than positive or neutral words, and this proportion could shrink with age). In fact, we considered alternative hypotheses whereby (i) children show heightened access to negative words due to their willingness to approach normatively "negative" stimuli (Grisanzio et al, 2020) and (ii) adolescents show an elevated negative valence bias due to normative peaks in risk for psychopathology and contrahedonic motivation in this developmental stage (Riedeger et al, 2009;Fairchild et al, 2011;McGrath et al, 2023). However, our findings did not support either alternative hypothesis and instead suggest that youth and adults are sampling from negative and positive words in similar proportions.…”
Section: Discussionmentioning
confidence: 99%
“…A likely explanation of this observation is that English has more negative emotion words than positive or neutral words (Jackson et al, 2021), although it may also be related to the classic literature showing that people typically attend more to negative than positive information (Rozin & Royzman, 2001). From a developmental perspective, negative valence bias may be especially elevated in childhood and decrease linearly across age, as prior research shows that children tend to seek out and attend to negative information more than other age groups (Grisanzio et al, 2020). Alternatively, the relationship between age and negative valence bias could be quadratic, such that negative valence bias peaks in adolescence, as is found for other clinical and affective processes that involve elevated focus on negative affect (e.g., risk of psychopathology ;Fairchild et al, 2011;McGrath et al, 2023;and contrahedonic motivation;Riediger et al, 2009).…”
Section: Introductionmentioning
confidence: 96%